How Operation Fistula uses data visualization to help women with obstetric fistula - Hollbrügge, Naledi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To enable all parts of Operation Fistula to make data-driven decisions in their work and to use data visualisation to simplify complex processes. Moreover, to effectively use data visualisation to educate the public about Obstetric Fistula and other issues of gender inequality. Methods: An experienced visual design analyst was hired full time to lead the analytics setup at the organisation and provide training for the team in the use of Tableau Desktop software. Results: Using a visual representation of data has spread information about Obstetric Fistula in an entirely new way to new audiences. One of our analyses has received over 10,000 views at this time. The use of data visualisation has created powerful partnerships for the organisation that have allowed Operation Fistula to raise significant funds and improve visibility of the cause. Staff members are now empowered to use data in their everyday work to make data-driven decisions. Conclusions: In a world that is driven by data, it is important that evidence-driven actions are implemented not only in the treatment of obstetric fistula but that we make data central to the everyday operation of our workplaces. Data visualisation is a powerful technique to make unfamiliar topics accessible, gain clarity on complex processes, and garner interest from otherwise unengaged actors. With new developments in commercial tools, data visualisation has become more accessible to every level of the business and is no longer exclusively the realm of data analysts.